(untitled) (International Journal of Engineering and Computer Science, 2016)
The one of the most important application for gathering specific information from the surrounding environment is WSN, so it is important to safeguard the sensitive data from unauthorized access. The security level in the WSN against the attacks in susceptible due to broadcast. There are two key attacks in WSN such as compromised node and denial of service.The key attack Compromised node(CN) attack which has the ability to create black hole, thereby interrupting the active information delivery and denial of service attack in attempt to make a network resource unavailable to its intended users, such as to temporarily or indefinitely interrupt or suspend services. In this paper we advance the mechanism that generate randomized multipath routes. In this mechanism that generate randomized multipath routes that means shares of different packets change over time. Incase the adversary came to know the routing algorithm,but it can’t identify the routes traversed by each packet more over randomness, the generated routes are also highly dispersive and energy efficient making them quite capable of bypass the black holes.